Duration of protection after first dose of acellular pertussis vaccine in infants - Quinn, H.; Snelling, Thomas; Macartney, K.; McIntyre, P. (American Academy of Pediatrics, 2014)
OBJECTIVE: Data on the effectiveness of the diphtheria- tetanus-acellular pertussis (DTaP) vaccine in the first 4 years of life are sparse. We evaluated the vaccine effectiveness (VE) of 1 and 2 doses of DTaP before 6 months of age and of 3 doses from 6 months of age in Australia, where, since 2003, a fourth dose is not given until 4 years. METHODS: We matched reported pertussis cases aged 2 to 47 months between January 2005 and December 2009 to controls from a population-based immunization register by date of birth and region of residence. VE by number of doses and age group was calculated as (1 - odds ratio) x 100%. RESULTS: VE against hospitalization increased from 55.3% (95% confidence interval [CI], 42.7%-65.1%) for 1 dose before 4 months of age to 83.0% (95% CI, 70.2%-90.3%) for 2 doses before 6 months. The VE of 3 doses of DTaP against all reported pertussis was 83.5% (95% CI, 79.1%-87.8%) between 6 and 11 months, declining to 70.7% (95% CI, 64.5%-75.8%) between 2 and 3 years of age and 59.2% (95% CI, 51.0%-66.0%) between 3 and 4 years of age. CONCLUSIONS: DTaP provided good protection against pertussis in the first year of life from the first dose. Without a booster dose, the effectiveness of 3 doses waned more rapidly from 2 to 4 years of age than previously documented for children > 6 years of age who had received 5 doses. Copyright © 2014 by the American Academy of Pediatrics.